A prospective, multicentre phase II trial of low-dose erlotinib in non-small cell lung cancer patients with EGFR mutations pretreated with chemotherapy: Thoracic Oncology Research Group 0911. Issue 14 (September 2015) - Yamada, Kazuhiko; Aono, Hiromi; Hosomi, Yukio; Okamoto, Hiroaki; Kato, Terufumi; Komase, Yuko; Nishikawa, Masanori; Azuma, Koichi; Takeoka, Hiroaki; Okuma, Yusuke; Nakahara, Yoshiro; Sato, Akira; et al.
Abstract: Background: Low-dose erlotinib may be as effective as gefitinib or erlotinib at full dose in non-small cell lung cancer (NSCLC) patients with activating mutations of the epidermal growth factor receptor ( EGFR ) gene. Methods: Patients with chemotherapy pretreated NSCLC harbouring EGFR mutations received erlotinib at 50 mg/d until disease progression or unacceptable toxicities. The dose was escalated to 150 mg/d in patients showing no response (i.e. without major tumour shrinkage according to Response Evaluation Criteria in Solid Tumours (RECIST)) to the initial dose during the first 4 weeks. The primary end-point was the objective response rate at the dose of 50 mg/d. Results: Thirty-four patients from seven institutes were enrolled. The study was closed early when no response was confirmed in 15 patients, excluding the possibility that the primary end-point would be met. The objective response and disease control rates at the dose of 50 mg/d as determined by an independent review committee were 54.5% and 84.8%, respectively. Four additional patients achieved partial response with increased 150 mg/d dose. Progression-free survival and median survival times during the entire period of the study were 9.5 and 28.5 months, respectively. Treatment-related toxicities were generally mild, the most common being skin disorders and diarrhoea. Only one case experienced grade 3 toxicity, which was transient increase of hepatic enzymes. Conclusion: The primary end-point was not met; low-dose erlotinib is not recommended for fit patients with NSCLC harbouring EGFR mutations. However, it may merit further evaluation for elderly or frail patients.